Empathy enhancement through group play therapy to reduce aggressive behavior - Iswinarti Iswinarti; Nurul Hidayah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
Aggressive behavior in children has negative impacts on their social life. The various intervention programs were used to reduce aggressive behavior, one of them was by enhancing children's empathy. Group Play Therapy is used to enhance children's empathy ability so that their aggressiveness level can decrease. This study aimed to enhance empathy through Group Play Therapy in children who had aggressive behavior. Experimental research was used with pre-test and post-test design in two different groups, the experimental and control groups. The subjects were twenty school-aged children. The subject’s criteria for having a moderate-low level of empathy, also having moderate-high levels of aggressiveness. The instruments were The LA Aggression Scale for Elementary School and Upper Secondary School Students to measure the aggression levels with Cronbach’s Alpha value is 0,879. The instrument used to measure the children’s empathy was The Empathy Questionnaire for Children and Adolescents (EmQue-CA) with Cronbach’s Alpha value is 0,828. The Wilcoxon, Mann-Whitney, and Kendall's Tau tests were used to analyze data. The results showed that Group Play Therapy can enhance children's empathy so that it can reduce aggressive behavior.